2009
DOI: 10.1159/000270917
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Salami Slicing: Pooled Analyses of Duloxetine for Depression

Abstract: Background: Publishing separate, yet very similar pieces of a single dataset across multiple papers is known as ‘salami slicing’. This practice may be motivated by researchers wishing to increase their publication counts and by the desire to increase exposure of their findings. ‘Salami slicing’ may also be used by the drug industry to help widely disseminate positive findings regarding its products. Journal editors across many scientific disciplines have bemoaned such duplicative publications on several occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 144 publications
0
31
0
1
Order By: Relevance
“…Academic authors (aka “key opinion leaders”) typically serve as authors, augmenting the credibility of journal articles via their perceived expertise and independence from the sponsor, which enhances the value of the drug brand [1,3]. Most research on duplicative publications has focused on overlapping publications of individual clinical trials [4], whereas pooled analyses have received scant attention [5]. …”
Section: Tablementioning
confidence: 99%
“…Academic authors (aka “key opinion leaders”) typically serve as authors, augmenting the credibility of journal articles via their perceived expertise and independence from the sponsor, which enhances the value of the drug brand [1,3]. Most research on duplicative publications has focused on overlapping publications of individual clinical trials [4], whereas pooled analyses have received scant attention [5]. …”
Section: Tablementioning
confidence: 99%
“…16 However, IRBs make these practices less common today. As another example, “salami slicing,” 17 publishing separate, but similar, articles that rely on the same set of data, has been described among trials of nonsteroidal anti-inflammatory drugs (NSAIDs) for rheumatoid arthritis, 18 of risperdone for psychosis, 19 and most recently, of duloxetine for depression. 17 However, the increased use of the internet and PubMed, the on-line MEDLINE search engine managed by the National Library of Medicine (NLM), makes this practice less common as well.…”
Section: Distortion Of the Medical Literaturementioning
confidence: 99%
“…74 James et al blame pharmaceutical company sales and marketing practices and uncritical reviewers at the New England Journal of Medicine of Merck-sponsored research that dismissed concerns of cardiovascular issues. 75 Spielmans et al examined the clinical trials on duloxetine, a treatment for depression, 76 to see how data were reported across 43 analyses, and found that in 88% of them at least one author was employed by a manufacturer of the drug and that six clinical trials were part of 20 or more separately published analyses.…”
Section: Conflicts Of Interestmentioning
confidence: 99%